2010
DOI: 10.1007/s11663-010-9418-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Small Additions of Tin on High-Temperature Oxidation of Fe-Cu-Sn Alloys for Surface Hot Shortness

Abstract: Steel produced in an electric arc furnace contains a high amount of copper (Cu) that causes a surface-cracking phenomenon called surface hot shortness. It is known that tin (Sn) can exacerbate the hot shortness problem. A series of iron (Fe)-0.3 wt pct Cu-x wt pct Sn alloys with an Sn content ranging from 0.03 to 0.15 wt pct was oxidized in air at 1423 K (1150°C) for 60 seconds, 300 seconds, and 600 seconds using thermogravimetry. A numerical model developed in a previous article was applied to predict the liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…The opposing effects of Ni and Sn are both related to their enrichment behavior at the oxide/metal interface, which were discussed in details in the previous papers: Ni enriches strongly in the cFe phase [11,15] whereas Sn enrich in the liquid phase [17]. The most detrimental effect of Sn results from the fact that its migration into the austenite grain boundary is aided by the liquid phase and this results in severe grain boundary decohesion [17].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The opposing effects of Ni and Sn are both related to their enrichment behavior at the oxide/metal interface, which were discussed in details in the previous papers: Ni enriches strongly in the cFe phase [11,15] whereas Sn enrich in the liquid phase [17]. The most detrimental effect of Sn results from the fact that its migration into the austenite grain boundary is aided by the liquid phase and this results in severe grain boundary decohesion [17].…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, the presence of Sn in the Cu-rich liquid was found to promote grain boundary penetration [15,16]. Sn at contents as low as 0.03 wt% causes significant grain boundary cracking [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, a lot of research have revealed the influence of copper alone or copper + tin on the oxidation behavior and surface hot shortness of steels and involved mechanism. [3][4][5][6][7][8][9][10] However, these studies almost focused on the copper content ranging from 0.25 wt% to 1.0 wt% instead of the lower copper content more commonly produced by electric furnaces, even the oxidation behavior and surface hot shortness of steels with the lower content of coexisted copper and arsenic. So far, Yin L. et al 11) has investigated the effect of 0.06 wt%-0.1 wt%As on oxidation behavior of Fe-0.3wt%Cu alloy in the (Received on January 2, 2016; accepted on March 17, 2016) To avoid surface hot shortness of C-Mn steels containing arsenic and copper + arsenic, high temperature oxidation behavior of the steels were systematically investigated.…”
Section: Introductionmentioning
confidence: 99%